A century of parasitology : discoveries, ideas, and lessons learned by scientists who published in the Journal of Parasitology, 1914-2014 - Janovy, John, Jr., 1937-; Esch, Gerald W. (Hoboken, New Jersey : Wiley, 2016)
"A celebration of the long shelf life and intellectual breadth of this journal, along with the rich history of parasitology, especially as manifest by American parasitologists and their colleagues from around the world"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Parasitology -- History; SCIENCE / Life Sciences / Zoology / General; Parasitology; History; Electronic books